No-Dose Photodynamic Therapy Against Half-Dose Photodynamic Therapy for Treatment of Central Serous Chorioretinopathy - Andrea Servillo; Riccardo Sacconi; Ilaria Zucchiatti; Elena Grachova; Lea Querques; Francesco Prascina; Beatrice Tombolini; Giorgio Dorin; Martin Mainster; Francesco Bandello; Giuseppe Querques (Ophthalmology and Therapy, 2023)
Abstract Introduction This study aimed to describe the effects of no-dose full-fluence photodynamic therapy without verteporfin (no-dose PDT) and to compare no-dose PDT with half-dose verteporfin full-fluence photodynamic therapy (HDFF PDT) for managing chronic central serous chorioretinopathy (cCSC). Methods This retrospective study evaluated 11 patients with chronic recurrent CSC treated with no-dose PDT between January 2019 and March 2022. Most of these patients were also treated with HDFF PDT a minimum of 3 months before and were considered as the control group. We described the changes of best corrected visual acuity (BCVA), maximum subretinal fluid (mSRF), foveal subretinal fluid (fSRF), and choroidal thickness (CT) 8 ± 2 weeks after no-dose PDT, and we compared BVCA, mSRF, fSRF, and CT of no-dose PDT with those of the of same patients previously treated with HDFF PDT. Results Fifteen eyes of 11 patients (10 male, mean age 54 ± 12 years) received no-dose PDT; among these, 10 eyes of 8 patients (7 male, mean age 53 ± 12 years) also received HDFF PDT. Three eyes showed complete resolution of fSRF after no-dose PDT. No significant differences were disclosed between treatment with and without verteporfin comparing BCVA, mSRF, fSRF, and CT at baseline and 8 ± 2 weeks from the treatment (p > 0.05 in all analyses). Conclusion BVCA and CT significantly improved after no-dose PDT. Short-term functional and anatomical treatment outcomes for cCSC were similar for HDFF PDT and no-dose PDT. We hypothesize that the potential benefits of no-dose PDT may arise from thermal elevation that triggers and enhances photochemical activities by endogenous fluorophores, activating a biochemical cascade response that rescues/replaces sick, dysfunctional retinal pigment epithelial (RPE) cells. Results of this study suggest the potential value of a prospective clinical trial to evaluate no-dose PDT for managing cCSC, especially when verteporfin is contraindicated or unavailable.